Optimization of flight distance for three types of javelin tip - Seo, K.; Kobayashi, T. (ISBS Proceedings Archive (Michigan), 2020)
In this study, optimization of javelin flight distance was carried out using a genetic algorithm. Javelin tips with three different shapes were designed within the confines of the regulations. The first design was that of a typical commercially available tip, whereas the second design was thinner and the third design thicker than the commercially available tip. The aerodynamic forces acting on the three types of javelin tip with respect to the angle of attack were calculated using a commercial solver. In the optimization study, the design variables were the initial conditions at release (determined by the thrower), and the objective function was the flight distance. The flight distance was calculated by numerical integration of the equations of motion. It was found that the flight distance for the thinner design was shorter than that for the other two types. The key to a longer flight distance is that in the first half of the flight the drag should be small (the angle of attack should be small) and in the second half of the flight the lift should be large (the angle of attack should be large).